Neisseria gonorrhoeae DNA bacterial load in men with symptomatic and asymptomatic gonococcal urethritis. (1st February 2017) - Priest, David; Ong, Jason J; Chow, Eric P F; Tabrizi, Sepehr; Phillips, Sam; Bissessor, Melanie; Fairley, Christopher K; Bradshaw, Catriona S; Read, Tim R H; Garland, Suzanne; Chen, Marcus
Abstract : Objective: Previous studies have quantified bacterial loads of Neisseria gonorrhoeae in the pharynx and rectum of men but not the urethra. We quantified the bacterial load of N. gonorrhoeae in men with symptomatic and asymptomatic urethral gonorrhoea infections. Methods: Consecutive men diagnosed with urethral gonorrhoea by Aptima Combo 2 testing of urine at the Melbourne Sexual Health Centre between March and July 2016 were eligible for the study: symptomatic men with purulent urethral discharge and asymptomatic men with no urethral symptoms. The gonococcal bacterial load in both groups was measured by urethral swab using a standardised collection method and real-time quantitative PCR targeting the opa gene. Results: Twenty men were recruited into the study: 16 had purulent urethral discharge and 4 had asymptomatic urethral gonorrhoea. The median gonococcal bacterial load was significantly higher among symptomatic men (3.7×10 6 copies per swab, IQR 2.5×10 6 –4.7×10 6 ) compared with asymptomatic men (2.0×10 5 copies per swab, IQR 2.7×10 4 –4.5×10 5 ) (p=0.002). Conclusions: Gonococcal loads in men with urethral discharge were higher than loads seen with asymptomatic urethral gonorrhoea and loads seen in asymptomatic pharyngeal and rectal gonorrhoea infections in previous studies.